THE EFFECT OF TEMPERATURE AND ALKALIZATION TIME ON CHANGES IN ACIDITY AND COLOR OF COCOA POWDER - Vivien Fathuroya; Bintoro, Nursigit; Devi Yuni Susanti; Arifin Dwi Saputro (Fakultas Teknologi Pertanian Universitas Brawijaya, 2026)
Natural cocoa powder needs to be processed with alkalizing technology to reduce acidity and darken the color to make it more suitable for industrial use. Two important factors that influence the alkalization process are temperature and duration time of the alkalization process. This research aimed to analyze the effect of temperature and duration time of alkalization process on changes in pH and color of alkalized cocoa powder. The research was designed using a completely randomized design, factorial 3x3, with 3 replications, where the first factor was the alkalization temperature (60, 80, and 100°C), and the second factor was the duration time of alkalization (15, 30, and 45 minutes). The results showed that alkalization was able to increase the pH and create a much darker color of cocoa powder, making it more suitable for industrial needs. The temperature and duration time, as well as the interaction of these two factors had a significant effect on the pH, L, a*, and b* values (p < 0.05). It was also obtained that the reaction rate constant (k) for pH was positive, while for the color components L, a*, and b* was negative, which meant that there was an increase in the pH value and a darkening of the color of cocoa powder during the alkalization process. Within the range of temperature and alkalization durations studied, the pH of the alkalized cocoa powder increased by 39.82-48.21%, compared with the natural cocoa powder. While L, a*, and b* decreased by 30.27-46.48%, 20.05-79.41%, and 22.23-71.21% compared to the natural cocoa powder, respectively. The k values ​​for the analyzed parameters varied between -0.0342 - 0.0112 minute-1. Meanwhile, the A and Ea values ​​were in the range of 0.03519 - 201.5220 minute-1 and 3.553 - 27.043 kJ.mol-1, respectively. The prediction equations for changes in pH and color components as a function of temperature and duration time obtained would be very useful for estimating the values of pH and color components of L, a*, and b* during the alkalization process